NOTE ON THE FECUNDITY AND SPAWNING PERIOD OF DREPANE PUNCTATA (LINNAEUS) - Pillai, P K Mahadevan; Devadoss, P (Indian Journal of Fisheries, 2011)
A brief account of thÂ« fecundity and spawning periodicity of Drepane punctata (Uniraeus) caught by the mechanised boats off Porto Novo is given. The number of eggs of D. punctata v/m estimiOed to range between 1,49,251 to 7,96,932. TTJC observations on stages of maturity during lune-September 1972 and ova-diameter frequency of intra-ovarian eggs suggest that there is a short and resected’ spawning period in this species.